A new approach for analysing the fuzzy system reliability using intuitionistic fuzzy number. (1st January 2011) - Kumar, Mohit; Yadav, Shiv Prasad; Kumar, Surendra
In general, fuzzy sets are used to analyse the fuzzy system reliability. In this paper, a new approach is developed for analysing the fuzzy system reliability of series and parallel systems using intuitionistic fuzzy set theory. For analysing the fuzzy system reliability, the definition of trapezoidal intuitionistic fuzzy number is introduced and arithmetic operations between two trapezoidal intuitionistic fuzzy numbers are also introduced. Also by considering several cases, it is shown that definitions of triangular intuitionistic fuzzy number, trapezoidal fuzzy number and triangular fuzzy number are the particular cases of the definition of trapezoidal intuitionistic fuzzy number introduced in this paper. For evaluating the fuzzy reliability of a series system and a parallel system, formulae are derived. For numerical verification of proposed approach, the fuzzy reliability of the basement flooding has been analysed using the proposed approach.